Involving Digital Transformations (DTs) in Sustainable Industrial Development: Challenge and Opportunities. - Kristianti, Tri; Aryanto Balol, Wirawan; Sunyoto (Prosiding Sains dan Teknologi, 2024)
Indonesia has implemented seventeen Sustainable Development Goals (SDGs) to achieve a better future in 2030. To support the ninth goal of SDGs which focuses on industry, innovation, and infrastructure, as the main framework, Digital Transformations (DTs) play a crucial role in developing the industrial need. Several companies apply Digital Transformations (DTs) to support revolutionary technology and human resources development. This research describes the companies’ challenges and opportunities to face readiness in the digital era, particularly for the industrial sector. PT. Kino Indonesia, PT. CS2 Pola Sehat, and PT. Santosa Utama Lestari (Japfa) were selected as the object of research due to the historical company background related to the application of modern technology. A case study is applied as the basic method to describe the cause and effect of Digital Transformations (DTs) for the company’s improvement. Data collection is gained based on interviews, indirect observations, and questionnaires. The description analysis will become a beneficial result as the reference for involving DTs in future sustainable industrial development.